Inovasi Layanan Kepegawaian Melalui Aplikasi E-Master pada Badan Kepegawaian Provinsi Jawa Timur - Ashari, Karina (Universitas Airlangga, 2020)
Abstract The implementation of quality public services needs to be carried out by the government in line with bureaucratic reform. The Regional Personnel Agency of East Java Province applies the Integrated Electronic State Civil Apparatus Management application (e-Master). The purpose of this paper is to describe the e-Master Innovation of the Regional Personnel Agency of East Java Province in terms of innovation attributes. The method used in this research is descriptive qualitative research method. The selection of informants was done by purposive sampling. Data obtained through interviews, observation and documentation. The data analysis technique used qualitative analysis. The result of the research is that using Rogers' innovation attribute theory, it is known that e-master innovation has helped overcome problems in the existing personnel management system. The ability of the system to store data and documents and is equipped with various integrated personnel services proves that the application of e-Master innovation can improve the quality of personnel services. Keywords: public service innovation, e-master, service quality Abstrak Penyelenggaraan pelayanan publik yang berkualitas perlu diselenggarakan pemerintah sejalan dengan reformasi birokrasi. Badan Kepegawaian Daerah (BKD) Provinsi Jawa Timur menerapkan aplikasi Manajemen aparatur sipil negara Terpadu Elektronik (e- Master). Tujuan paper ini adalah mendeskripsikan Inovasi e-Master Badan Kepegawaian Daerah (BKD) Provinsi Jawa Timur ditinjau dari atribut inovasi. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif deskriptif. Pemilihan informan dilakukan dengan purposive sampling. Data didapatkan melalui wawancara, observasi dan dokumentasi. Teknik analisis data menggunakan analisis kualitatif. Hasil penelitian adalah menggunakan teori atribut inovasi Rogers diketahui bahwa inovasi e- master telah membantu mengatasi permasalahan dalam sistem manajemen kepegawaian yang ada sebelumnya. Kemampuan sistem dalam menyimpan data dan dokumen serta dilengkapi dengan berbagai layanan kepegawaian yang telah terintegrasi membuktikan bahwa penerapan inovasi e-Master dapat meningkatkan kualitas pelayanan kepegawaian. Kata kunci: inovasi pelayanan publik, e-master, kualitas pelayanan